THE AUTOMATIC LIGHTENING LOCATION SYSTEM AND ITS IMPLICATIONS FOR THE NIGERIAN ELECTRONIC POWER SYSTEM (Nigerian Journal of Technology, 2003)
The incidence of cloud-to-ground lightening flashes in a usual occurrence during thunderstorms. In order to minimize the numerous hazards caused by lightening on electric power systems, knowledge of the lightening phenomenon is necessary. In most tropical countries including Nigeria, the frequency of lightening flashes is fairly high and the lightening ground flash in known to be responsible for the vast majority of power outages experienced in the power supply systems of these countries. An automatic lightening location system of the lightening Location and Protection (LIP) type has been used in Sweden to investigate some parameters of ground flashes. The results obtained are presented and analysed. The application of lightening information to electric power system is also discussed. Lightening data is found to be very useful for proper planning and operation of power systems. The implications of the lightening location system for the Nigerian electric power system are also highlighted.